2019
DOI: 10.1111/ases.12710
|View full text |Cite
|
Sign up to set email alerts
|

Detection of indocyanine green fluorescence to determine tumor location during laparoscopic gastrectomy for gastric cancer: Results of a prospective study

Abstract: Introduction In laparoscopic gastrectomy, a method to locate the margin of an early‐stage cancerous lesion that is invisible from the serosal surface and impalpable during laparoscopic procedures is needed to determine an appropriate transection line. We conducted a prospective study to develop a new marking method using preoperative submucosal injection of indocyanine green (ICG). Methods Patients undergoing laparoscopic gastrectomy for T1 gastric cancer were recruited. The first 11 patients comprised the lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…ICG fluorescence laparoscopy has been applied in gastrointestinal surgery in recent years. Several studies have found that, in gastric cancer surgery, preoperative smaller doses of ICG injection in the submucosa around the tumor are conducive to clear imaging of tumor location intraoperatively, and indicate that ICG fluorescence laparoscope could be used to determine the accurate position of intraoperative tumors (18)(19)(20). These studies support the findings of the present study.…”
Section: Discussionsupporting
confidence: 90%
“…ICG fluorescence laparoscopy has been applied in gastrointestinal surgery in recent years. Several studies have found that, in gastric cancer surgery, preoperative smaller doses of ICG injection in the submucosa around the tumor are conducive to clear imaging of tumor location intraoperatively, and indicate that ICG fluorescence laparoscope could be used to determine the accurate position of intraoperative tumors (18)(19)(20). These studies support the findings of the present study.…”
Section: Discussionsupporting
confidence: 90%
“…This NIR imager produces pictures with a superior fluorescent signal contrast than the imaging system used in our study [27]. Currently, there is no consensus on the ICG concentration required for submucosal GI tattooing and the literature has a large dose variability [13][14][15][16][17][18]. The ICG dosing chosen for our study was the same utilized in the successful work by Ushimaru et al on gastric tumor tattooing [14].…”
Section: Discussionmentioning
confidence: 99%
“…The main advantage of ICG over non-fluorescent dyes (India ink and SPOT™) is that, in cases of intraperitoneal spillage, the surgical dissection planes are potentially less compromised under white light. For this reason, several authors have recently successfully used ICG as an efficient and safe alternative gastrointestinal tattooing method in clinical trials [13][14][15][16][17][18]. However, in most of those trials, the endoscopic ICG tattooing was performed 1 to 3 days preoperatively which is clinically improbable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results of fluorescent marking with ICG were presented by Ushimaru et al; 16 in a group without ICG injection, a positive resection margin was found in 5% of cases, whereas in a group with ICG tumor position marking, it was found in 0% of cases. Tanaka et al 17 proposed a dosage of 0.1 mL at a concentration of 0.5 mg/mL for optimal visualization of injection sites. Diameters of ICG injection sites were much smaller (i.e., 21 mm) than historical controls with India ink (52 mm).…”
Section: Introductionmentioning
confidence: 99%